Understanding water uptake in sugar beet - Fitters, Tamara F.J. (2019)
Sugar beet is grown worldwide for sugar production. In the UK the main growing area is East Anglia, which has an annual rainfall of c.600 mm and the crop is predominantly growth on sandy loam soils. Previous work has reported that sugar beet shows an average annual yield loss of 10% due to water deficits and during dry years this loss can increase up to 25%. It was also found that sugar beet can grow roots up to 1.5m deep but there is hardly any water uptake from depth which might contribute to yield loss due to drought stress.